Killer: Alex Delaware #29 #29 - Kellerman, Jonathan (New York : Ballantine Books, 2014)
"Well-used to elevated emotions, psychologist Alex Delaware shrugs off a joking death threat from beautiful Beverly Hills physician Constance Sykes, whose attempt to secure legal custody of her baby niece is thwarted by Alex's forthright report to the court. Alex plays down the threat until LAPD's Milo Sturgis rushes to his side with the shocking word on the street that a hit's been taken out on him. But while Alex may be in grave danger, it won't be from the Beverly Hills doctor, for Connie's soon discovered brutally slain. When her sister Cherie and the baby disappear, apparently on the run, Alex's search for answers lead him to aged rockers, charming homeboys and even Machiavellian judges. As the darkest of secrets are peeled away, and a cruel system churns through family lives, Alex seeks to stop a vicious killer and save a child from a life of nightmares ... or worse"--.
Keywords: Delaware, Alex (Fictitious character) -- Fiction; Sturgis, Milo (Fictitious character) -- Fiction; Police -- California -- Los Angeles -- Fiction; Mentally ill offenders -- Fiction; Serial murders -- Fiction; Psychologists -- Fiction; Psychopaths -- Fiction; FICTION / Suspense; FICTION / Mystery & Detective / General; FICTION / Thrillers; Los Angeles (Calif.) -- Fiction; Mystery fiction; Suspense fiction; Psychological fiction